2019
DOI: 10.1016/j.invent.2019.100285
|View full text |Cite
|
Sign up to set email alerts
|

The Therapist-assisted Online Parenting Strategies (TOPS) program for parents of adolescents with clinical anxiety or depression: Development and feasibility pilot

Abstract: ObjectiveTo develop a Therapist-assisted Online Parenting Strategies (TOPS) program that is acceptable to parents whose adolescents have anxiety and/or depressive disorders, using a consumer consultation approach.MethodsThe TOPS intervention was developed via three linked studies. Study 1 involved content analysis of feedback from participants (N = 56) who received a web-based preventive parenting intervention called Partners in Parenting (PiP), as part of a randomised controlled trial. Study 2 involved stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…with TMH). Overall, most of studies here retrieved demonstrated the superiority of TMH interventions over the placebo or a comparable efficacy of TMH intervention to face-to-face modality with regards to studies on youth anxiety [ 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] depression [ 9 , 21 , 38 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 83 , 84 , 85 , 86 ] or OCD [ 70 , 71 , 73 , 74 , 75 , 76 , 77 , 87 ]. Comput...…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…with TMH). Overall, most of studies here retrieved demonstrated the superiority of TMH interventions over the placebo or a comparable efficacy of TMH intervention to face-to-face modality with regards to studies on youth anxiety [ 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] depression [ 9 , 21 , 38 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 83 , 84 , 85 , 86 ] or OCD [ 70 , 71 , 73 , 74 , 75 , 76 , 77 , 87 ]. Comput...…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parent-focused Internet-delivered CBT appear to be as well effective as an early intervention in treating preschool-age children with anxiety disorders in a modified version of the BRAVE-ONLINE program [ 31 ]. Studies including mixed samples (i.e., individuals with anxiety and depressive symptomatology) similarly reported improvements in both clinical dimensions [ 37 , 40 , 41 , 42 , 43 , 46 , 83 ]. Moreover, both computer-based and therapist-delivered online psychotherapy (i.e., cognitive behaviour therapy, CBT) for youth depression have been demonstrated to be effective, cost-effective and very comparable with face-to-face treatment [ 49 , 50 , 51 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations